The effect of Aloe ferox Mill. in the treatment of loperamide-induced constipation in Wistar rats - Wintola Olubunmi A (BMC Gastroenterology, 2010)
Abstract Background Constipation is the most common gastrointestinal complaint all over the world and it is a risk factor of colorectal cancer. In this study, the efficacy of aqueous leaf extract of Aloe ferox Mill. was studied against loperamide-induced constipation in Wistar rats. Methods Constipation was induced by oral administration of loperamide (3 mg/kg body weight) while the control rats received normal saline. The constipated rats were treated with 50, 100 and 200 mg/kg body weight/day of the extract for 7 days during which the feeding characteristics, body weight, fecal properties and gastrointestinal transit ratio were monitored. Results The extract improved intestinal motility, increased fecal volume and normalized body weight in the constipated rats, which are indications of laxative property of the herb with the 200 mg/kg body weight of the extract showing the best efficacy. Conclusion The effect of the extract compares favourably well with senokot, a standard laxative drug. These findings have therefore, lent scientific credence to the folkloric use of the herb as a laxative agent by the people of the Eastern Cape of South Africa.